2020
DOI: 10.1186/s13568-020-01070-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-supplemented propagation of Saccharomyces cerevisiae improves its lignocellulose fermentation ability

Abstract: Propagation conditions have been shown to be of considerable importance for the fermentation ability of Saccharomyces cerevisiae. The limited tolerance of yeast to inhibitors present in lignocellulosic hydrolysates is a major challenge in second-generation bioethanol production. We have investigated the hypothesis that the addition of nutrients during propagation leads to yeast cultures with improved ability to subsequently ferment lignocellulosic materials. This hypothesis was tested with and without short-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
1
13
0
3
Order By: Relevance
“…In our previous work, we noted the importance of detoxification of the medium from aldehydes to allow the growth of S. cerevisiae [ 18 ]. Therefore, the differential expression of genes encoding oxidoreductases that have been shown to have activity on furfural and HMF was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous work, we noted the importance of detoxification of the medium from aldehydes to allow the growth of S. cerevisiae [ 18 ]. Therefore, the differential expression of genes encoding oxidoreductases that have been shown to have activity on furfural and HMF was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…6 B), are genes encoding proteins involved in the synthesis of the thiamin precursor hydroxymethylpyrimidine [ 66 ]. In a previous study, we showed that supplementing non-adapting cultures with a mixture of thiamin and pyridoxine improves fermentation performance in hydrolysate-containing medium [ 18 ]. Apart from a protein of unknown function (DPA10), three out of four genes that showed a trend of down-regulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…) and vitamins (e.g., thiamine (B1), pyridoxine (B6), biotin (B7), riboflavin, nicotinic acid (B3), pantothenic acid (B5), etc. ), which significantly impact yeast growth, stress tolerance, ethanol yield, and secondary synthesis of fermentation metabolites (Venkateshwar et al, 2010;Perli et al, 2020;van Dijk et al, 2020). Moreover, nitrogen compounds such as amino acids and proteins stimulate yeast growth and improve fermentation kinetics.…”
Section: Introductionmentioning
confidence: 99%